Changing infection control behaviour in Egypt - Badawi, Hala; El Said, Manal (International Journal of Infection Control, 2008)
The infection control unit at the Theodor Bilharz Research Institute in Egypt describes how it responded to the challenge of changing a culture of infection control practice in the workplace. Improved disposal of healthcare waste, the introduction of hand hygiene facilities and the design of a central sterilisation unit are some of the measures being introduced to raise awareness of infection control in the institute. The team also found that mupirocin nasal applications on healthcare workers with MRSA colonisation resulted in nasal carriage clearance.